1995
DOI: 10.1093/infdis/171.5.1190
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Neurologic Manifestations of Primary Human Immunodeficiency Virus Infection on Disease Progression

Abstract: To determine the influence of neurologic manifestations of primary human immunodeficiency virus (HIV) infection on disease progression, 277 nonhemophiliac adults enrolled < 1 year after HIV infection were studied. Patients with neurologic manifestations during symptomatic primary HIV infection (PSI) (group N+; n = 23), with nonneurologic manifestations (group N-; n = 112) during PSI, and without any clinical manifestation during primary infection (group NPI; n = 142) were compared for disease progression. Age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 0 publications
1
29
1
Order By: Relevance
“…33 Individuals with neurological manifestations of primary HIV infection should initiate cART as these manifestations are associated with accelerated progression of HIV. 34 Initiation of cART during primary infection may have long-term benefits by reducing the latent viral reservoir, lowering the viral set point and preserving immune function and can potentially reduce transmission. 35 Although data on the effect of cART in reducing the risk of severe complications of primary HIV infection are lacking, we believe that patients presenting with CNS symptoms as part of a primary infection should be offered .500,000 …”
Section: Discussionmentioning
confidence: 99%
“…33 Individuals with neurological manifestations of primary HIV infection should initiate cART as these manifestations are associated with accelerated progression of HIV. 34 Initiation of cART during primary infection may have long-term benefits by reducing the latent viral reservoir, lowering the viral set point and preserving immune function and can potentially reduce transmission. 35 Although data on the effect of cART in reducing the risk of severe complications of primary HIV infection are lacking, we believe that patients presenting with CNS symptoms as part of a primary infection should be offered .500,000 …”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20% of individuals with primary human immunodeficiency virus type 1 (HIV-1) infection syndrome have symptoms of viral meningitis (2,5,23,38). HIV-1 infection of the brain occurs early, whereas HIV-associated dementia (HAD) generally develops only in late-stage HIV-1 disease (Ͻ50 CD4 cells/l) (23).…”
mentioning
confidence: 99%
“…In most studies of risk factors for progression, the endpoint is the onset of AIDS. Epidemiological studies have suggested a shorter AIDS incubation period in patients with symptomatic primary infection (SPI) 3,4 and among homosexual patients (relative to heterosexuals 5 and haemophiliacs 6 ). To date, age at infection is the most widely recognized risk factor for progression to AIDS.…”
mentioning
confidence: 99%